The Italian instructions for the design, execution and control of timber constructions (CNR-DT 206 R1/2018). (15th February 2022) - Faggiano, Beatrice; Sandoli, Antonio; Iovane, Giacomo; Fragiacomo, Massimo; Bedon, Chiara; Gubana, Alessandra; Ceraldi, Carla; Follesa, Maurizio; Gattesco, Natalino; Giubileo, Costantino; Pio Lauriola, Marco; Podestà, Stefano; et al.
Highlights: Latest experimental, theoretical and technological advancements from research are considered. New timber products (CLT panels, Solid Wood Panels (SWP) and glued solid panels) are included. Design rules for structural elements, types, systems and for multi-story buildings are given. Seismic design rules for non dissipative and dissipative structures are provided. Mechanical and carpentry joints, structural robustness and existing structures are introduced. Abstract: In 2007 the Italian National Research Council published the technical document CNR-DT 206/2007 "Instructions for the design, execution and control of timber structures", with the purpose to provide a technical support to the operators of the sector, in line with the most advanced knowledge at that time. Since then, the world of timber engineering has largely used such document, even though the instructions are not mandatory standard rules, so that they became the most common tool in Italy for the structural use of timber, opening the markets and favouring competition and new applications. In latest years new studies, researches and innovative proposals have promoted the development and the growth of timber constructions also in the civil residential field. The framework of standard rules for constructions and products, both Europeans and Italians, has evolved too. For these reasons, CNR has considered as opportune to proceed to the editing of a new version, updated and widened, namely with the acronym DT 206-R1. The document comes from the spontaneous cooperation of an open group of specialists and operators of the sector, based on a wide discussion on the common scientific and technical expertise and knowledge. The current version has already taken into account the results of the public inquiry phase (concluded by now). The paper presents the main contents of the document, evidencing the innovations.